Methods of treating and/or preventing major adverse cardiovascular event (MACE) with combination of BET bromodomain inhibitor and sodium-dependent glucose transporter 2 inhibitor - HALLIDAY CHRISTOPHER ROSS ARMSTRONG; LEBIODA KENNETH EUGENE; KHAN AWAZ NADEEM (2022)
Described herein are methods of treating and/or preventing a major adverse cardiovascular event (MACE) by administering to a subject in need thereof a combination of a sodium-glucose transporter 2 (SGLT2) inhibitor and a compound of Formula I, wherein the variables of Formula I are as defined herein, or a stereoisomer, tautomer, pharmaceutically acceptable salt or hydrate thereof. 本文描述了通过向有需要的个体施用钠-葡萄糖转运蛋白2(SGLT2)抑制剂和式I化合物或其立体异构体、互变异构体、药学上可接受的盐或水合物的组合来治疗和/或预防主要不良心血管事件(MACE)的方法，其中式I的变量如本文所定义。